Musical Effect and Personality: The Impacts of Video Game Music on Task Performance of Different Personality Dimensions - Anný Tinna Aubertsdóttir 1993- (2018)
This study was conducted to examine the effects of video game music on cognitive task performance for individuals scoring high and low on the various personality dimensions as measured with NEO-FFI. The participants of the study consisted of 70 undergraduate psychology students from the age 19 to 37, 18 men (25,7%) and 52 women (74,3%) all students at Reykjavik University. There were two experimental conditions to collect data about the impact of music, silence vs. low volume video-game music. Participants were randomly assigned to either silent condition or musical condition, where they all solved four levels of Stroop test. To gather information about the personality type, participants answered the revised NEO personality inventory that consists of 60 questions. The results showed significant main effect for the Extroversion, and significant interactions for Neuroticism and Agreeableness personality dimensions. Where Neuroticism showed the most significant effects, i.e. Individuals who scored high on neuroticism performed well on all levels of the Stroop test in the silence condition. However, when they were exposed to music, scores were significantly worse compared to those who scored low on neuroticism. There was also a particular trend in the difficulty levels of the Stroop test and the increasing importance of silence for all of the personality dimensions. Keywords: musical effect, personality types, the five-factor inventory, Stroop effect, task performance, focus, attention Rannsóknin var framkvæmd til að kanna áhrif tölvuleikjatónlistar á hugræna færni mismunandi persónuleika við úrlausn taugasálfræðilegs verkefnis. Úrtakið innihélt 70 þátttakendur, allt nemendur við Háksólann í Reykjavík. Alls voru 18 karlkyns þátttakendur og 52 kvennkyns þátttakendur. Það voru tvennskonar rannsóknaraðstæður til þess að safna gögnum um áhrif tónlistar, þ.e. þögn vs. lágt stillt tölvuleikjatónlist. Þátttakendum var handahófskennt skipt í aðstæður, þar sem þeir leystu fjórar gerðir af Stroop prófi. Gagnasöfnun fyrir ...